2008
DOI: 10.1292/jvms.70.429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bovine Lactoferrin on Functions of Activated Feline Peripheral Blood Mononuclear Cells During Chronic Feline Immunodeficiency Virus Infection

Abstract: ABSTRACT. Feline immunodeficiency virus (FIV) infection is characterized by chronic overactivation of immune and inflammatory system, resulting in anergic state and dysfunction of immune cells. Lactoferrin (LF), a glycoprotein present in exocrine secretions and neutrophils, plays an important role in host defense system. Our previous study showed that oral administration of bovine LF (bLF) suppressed oral inflammation, improved the clinical symptoms and decreased serum γ-globulin as a marker of inflammation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…4). This finding is consistent with published studies demonstrating that Lac suppressed mitogen Con A or phytohaemagglutinininduced cell proliferation and expression of IFN-g by peripheral blood mononuclear cells and splenocytes in vitro (32,33).…”
Section: Viral and Autoimmune Hepatitis As Well As Other Types Of Immsupporting
confidence: 93%
“…4). This finding is consistent with published studies demonstrating that Lac suppressed mitogen Con A or phytohaemagglutinininduced cell proliferation and expression of IFN-g by peripheral blood mononuclear cells and splenocytes in vitro (32,33).…”
Section: Viral and Autoimmune Hepatitis As Well As Other Types Of Immsupporting
confidence: 93%
“…The addition of 500 µg/ml bLf after ConA significantly inhibited the expression of IFN-γ and IL-2 in FIV-positive cats. This study suggested that treatment with bLf could maintain the immune homeostasis of immunosuppressed FIV-positive cats [76].…”
Section: In Vivo Assaysmentioning
confidence: 70%
“…It has been reported that oral administration of bLf suppressed oral inflammation in feline immunodeficiency virus FIV-infected cats with intractable stomatitis infection. This result suggests that bLf therapy may have a potential application to improve and protect functions of overactivated lymphocytes by modulating the cell proliferation, cell cycle and cytokines expression as shown in cats in terminal stage of FIV infection [ 88 ].…”
Section: Inhibition Of Viral Infections By Lactoferrinmentioning
confidence: 99%